Influence of Tigernuts on the Antioxidant Vitamins Levels in Normal Weight Male Human Subjects - Edokpolor N, Igbinovia; Wisdom O, Ohiwerei; Festus Oloruntoba O; Onokevbagbe Elisha I; Adisa W A (International Journal of Applied and Scientific Research, 2024)
Tubers have been recognized as a valuable source of essential macro- and micronutrients vital for overall health. Among these, tigernut has been gaining popularity due to its rich composition. This tuber contains bioactive compounds such as sterols, alkaloids, tannins, saponins, resins, and vitamins E and C. Natural antioxidants have attracted significant attention from nutritionists, food manufacturers, medical professionals, and consumers due to their numerous health benefits. This study aimed to examine the effect of tigernuts on human vitamin A, C, and E levels in normal-weight male subjects under resting conditions, as well as to explore potential mechanisms of action. Methods: The study involved forty (40) male participants who were non-habitual tigernut consumers, aged 18–28 years. Anthropometric data were recorded for control subjects, who then rested for 1 hour and 30 minutes. Serum vitamin C levels were analyzed using a spectrophotometric method, with ascorbic acid showing maximum absorption at 478.5 nm in methanolOn a separate day, each participant was given 5g of tigernut to chew as a bolus, with the same subjects serving as both control and test participants.The findings revealed that tigernut consumption significantly increased (P < 0.05) vitamin E levels from 0.09573 ± 0.021 to 0.8430 ± 0.057 mg/%. In contrast, vitamin A levels significantly decreased (P < 0.05) from 291.8 ± 29.50 to 97.89 ± 32.36 mg/%. Vitamin C levels also declined post-consumption, from 1.586 ± 0.201 to 1.188 ± 0.080 mg/%, though this decrease was not statistically significant.The results suggest that tigernut consumption enhances vitamin E levels while reducing both vitamin A and C levels in normal-weight male subjects